Fluoroquinolone resistance mutations among Mycobacterium tuberculosis and their interconnection with treatment outcome - Ramakant Dixit; Emil Mohan; Ankur Gupta; Priyanka Soni Gupta; Tarun Patni; Mukesh Goyal; Roshan Kumar Meena (International Journal of Mycobacteriology, 2023)
Background: Fluoroquinolone (FQ) antibiotics are among the most potent second-line antitubercular drugs these days. The aim of the study was to analyze the frequency and pattern of genetic mutation in preextensive (pre-XDR) and extensively drug-resistant Mycobacterium tuberculosis using second-line line probe assay (LPA) and to compare drug-resistant mutations with different treatment outcomes. Methods: Sputum, lymph node aspirate, and cold accesses from patients with rifampicin-resistant Tuberculosis (TB) were subjected to first-line and second-line LPA (Genotype MTBDRsl by Hain Life Science, Germany) to assess additional drug resistance to fluoroquinolones (levofloxacin and moxifloxacin). Final treatment outcomes as per the National TB Elimination Program were assessed and compared with the mutation profile. Results: One hundred and fifty subjects were observed to have mutations associated with resistance to FQs and constituted the final study population. The most frequent mutation observed among GyrA drug resistance mutation was D94G (Gyr A MUT3C, 44/150, 66%) corresponding to high-level resistance to levofloxacin and moxifloxacin. The same mutation was associated with poor treatment outcome as died or treatment failure (odds ratio 2.50, relative risk 1.67, P = 0.043). The most common hetero-resistance mutation pattern observed in GyrA gene was wild type plus Asp94Gly mutation in 24.6% of isolates. Conclusions: GyrA MUT3C hybridization corresponding to single-point mutation of aspartic acid to glycine at codon 94 constitutes the most common mutation in GyrA gene locus in M. tuberculosis with significant association with treatment outcome as died compared to those with treatment outcome as cured.